ETNOMATEMATIKA: IDENTIFIKASI BATIK GAJAH OLING BERDASARKAN KONSEP GEOMETRI - Erfan Yudianto; Titik Sugiarti; Sunardi Sunardi; Karima Salasari (JPMI (Jurnal Pendidikan Matematika Indonesia), 2021)
Abstract. Ethnomathics is a multicultural mathematics activity that uses culture to make connections with distinctive mathematical topics, so as to motivate students to investigate and preserve their own culture while learning mathematics. The purpose of this research is to explore the ethnomatematics contained in Gajah Oling batik based on the concept of geometry and to produce teaching material products in the form of student project sheets. This type of research is qualitative with an ethnographic approach. The data collection methods used were observation and interviews. The research subjects were 1 person, namely a designer and an isen-isen batik maker from Gajah Oling. Ethnomatematics appears both in the results of batik and in the process of making designs and isen-isen. At the isen-isen stage, the concept of points and lines appears, while at the stage of making Gajah Oling's batik designs, the concepts of angles, flat shapes, congruence and congruence, geometric transformations which include translation, rotation, reflection, and dilation appear.Keywords: Ethnomatematic, Gajah Oling’s Batik, Geometry, Geometry Transformation